On the supramacromolecular structure of core–shell amphiphilic macromolecules derived from hyperbranched polyethyleneimine - Picco, Agustin Silvio (2014)
The supramacromolecular structure of core–shell amphiphilic macromolecules (CAMs) with hyperbranched polyethyleneimine (HPEI) cores and fatty acid chain shells (HPEI-Cn) for different chain lengths was investigated both, in colloidal suspension, solid phase and at the air–water interface using Small Angle X-ray Scattering (SAXS), Wide Angle X-ray Scattering (WAXS), X-ray Reflectometry (XRR) and Langmuir isotherms. At low temperatures colloidal toluene suspensions of the HPEI-Cn polymers form, as evidenced by peaks arising in the structure factor of the system showing mean particle-to-particle distances correlated with the length of the aliphatic chains forming the shells of HPEI-Cn unimicelles. The CAM sizes as found from the SAXS experiments also display a clear dependence on shell thickness suggesting that the aliphatic chains adopt a brush-like configuration. After solvent extraction, HPEI-Cn adopts ordered structures with hexagonal packing of the aliphatic chains. Submitted to lateral pressure Π at the air–water interface, HPEI-Cn undergoes a disorder–order transition with increasing transition pressure for increasing chain lengths. The CAMs show different behaviors in-plane and out-of-plane. While out-of-plane the aliphatic chains behave as a brush remaining almost fully unfolded, whereas parallel to the air–water interface the chains fold down in a mushroom way with increasing lateral pressure Π.